Agricultural and food processing wastes - International Symposium on Agricultural and Food Processing Wastes (6th : 1990 : Chicago, Ill.); Schulte, Dennis D.; American Society of Agricultural Engineers (St Joseph, MI : American Society of Agricultural Engineers, 1990)
10